The investigation of bourgeois pedagogy: an essay on the contributions of the Gramscian framework to research (PerCursos, 2024)
This essay presents a synthesis of the theoretical-methodological references produced from Gramsci's writings. His concept of the “Integral State” is presented as an investigation tool for comprehend the role of education in achieving the project of bourgeois domination. The thoughts presented take as its central axis the possibility of using his work to understand the pedagogical strategies and practices of the bourgeoisie, its organizations and intellectuals. They have the intention to systematically form the “new man”, whose "psychophysical nexuses" are constantly calibrated to the frequent historical transformations of the mass production process and also to the changes in the reproduction of the processes of domination in the face of the contradictions and crises of capitalism. It is also presented Gramsci's historical updating of the Marxist method of analysis, comprehending that Lenin’s works and his orthodox reading of Marx´s writings made possible advances in this analysis. Bringing his theorical framework into more recent historical contexts, we see how the superstructural duo - political society and civil society - has expanded considerably in the concrete reality of social struggles. We conclude this article by emphasizing that, within the limits of this text, we have highlighted a set of theoretical references that have been supporting collective research into the role of education in bourgeois strategies for domination.
Keywords: Gramsci; integral State; political pedagogy; business community; education